Viral Vectors for the Induction of Broadly Neutralizing Antibodies against HIV - Sarah Wilmschen (Vaccines, 2019)
Extensive research on generating an efficient HIV vaccine is ongoing. A major aim of HIV vaccines is the induction of long-lasting, broadly neutralizing antibodies (bnAbs) that can confer sterile immunity for a prolonged period of time. Several strategies have been explored to reach this goal, i.e. protein immunization, DNA, or viral vectors, or a combination thereof. In this review, we give an overview of approaches using viral vectors for the induction of HIV-specific bnAbs. Many pre-clinical studies were performed using various replication-competent and -incompetent vectors. Amongst them, poxviral and adenoviral vectors were the most prevalent ones. In many studies, viral vectors were combined with a DNA prime or a protein boost. However, neutralizing antibodies were mainly induced against the homologous HIV-1 vaccine strain or tier 1 viruses, and in rare cases, against tier 2 viruses, indicating the need for improved antigens and vaccination strategies. Furthermore, we also review next generation Env antigens that are currently being used in protein vaccination approaches and point out how they could be utilized in viral vectors.